A NEW SET OF FIRST WORLD WAR DIARIES FOR THE MESOPOTAMIA CAMPAIGN, FEBRUARY 1916 TO JUNE 1917. Issue 1 (1st April 2021) - MacLellan, Rory
Abstract : Two diaries written by a Territorial Force officer serving in Mesopotamia from 1916 to 1917 have been recently discovered. They contain valuable insight into the difficulties and dangers of life on campaign, an account of the action of As Sahilan (11 September 1916), and what appears to be a unique description of the escort of an Ottoman princeling to a prisoner-of-war camp. These diaries help shed light on a theatre of the First World War that is often overlooked in favour of the Western Front. This paper presents some of the most interesting entries and discusses their significance.